The impact of modifiable health metrics on mortality for older adults with low cognitive function - Wang, Wei; Sun, Pengfei; Lv, Tingting; Li, Min (Frontiers in Public Health, 2024)
Objectives: Cognitive impairment has emerged as a major contributing factor to mortality for older adults. Identifying the strong modifiable health metrics against mortality is of high priority, especially in this high-risk population.: This population-based study used data of US adults aged≥60 years old from the National Health and Nutrition Examination Survey 2011-2014 cycles. De-identified data for participants who completed cognitive function test were extracted. Mortality data was obtained by linking to the 2019 public-use linked mortality file.Results: Participants with low global cognition had higher risk of all-cause mortality (HR=1.46; 95%CI, 1.04-2.05). The highest prevalence of ideal level of health metrics was observed for sleep duration (54.36% vs. 62.37%), and the lowest was noted for blood pressure (12.06% vs. 21.25%) for participants with low and average to high global cognition, respectively. Ideal status of physical activity and diet quality were significantly associated with all-cause mortality among participants with low global cognition (HR=0.48, 95%CI: 0.28-0.82; HR=0.63, 95%CI: 0.43-0.95). The corresponding population-attributable fractions were 26.58% and 15.90%, respectively.Low cognitive function was associated with increased risk of all-cause death for older adults. Attainment of healthy metrics, especially sufficient physical activity, consuming healthy diet and being never smoked, provided strong protection against death risk.